Biodosimetry, can it find its way to the nuclear medicine clinic? - Bolcaen, Julie; Combrink, Nastassja; Spoormans, Kaat; More, Stuart; Vandevoorde, Charlot; Fisher, Randall; Kleynhans, Janke (Frontiers in Nuclear Medicine, 2023)
Personalised dosimetry based on molecular imaging is a field that grew exponentially in the last decade due to the increasing success of Radioligand Therapy (RLT). Despite advances in image-based 3D dose estimations, the administered dose of a therapeutic radiopharmaceutical for RLT is often non-personalized, with standardised dose regimes administered every 4-6 weeks. Biodosimetry markers, such as chromosomal aberrations, could be used alongside image-based dosimetry as a tool for individualised dose estimations to further understand normal tissue toxicity and refine the administered dose. In this review we give an overview of biodosimetry markers that are used for blood dose estimations, followed by an overview of their current results when applied in RLT patients. Finally, an indepth discussion will give a perspective on the potential for the use of biodosimetry in the nuclear medicine clinic.